Potential Seismogenic Faults in Norway - Smirnova, Kristina (The University of Bergen, 2019)
Identification of seismogenic potential of faults in an area is crucial in the assessment of earthquake hazard. One of the most challenging tasks in seismotectonic analysis that leads to the identification of the seismogenic potential of earthquake sources, is to correlate faults to seismicity. Significant number of studies are performed for areas experiencing high level of seismic activity, such as active plate boundaries. However, there are limited efforts in areas experiencing low level of seismic activity, such as intraplate settings, such as Norway. Therefore, analysis of seismogenic potential of faults is crucial and necessary, since large and destructive earthquakes have been documented in intraplate settings earlier. In Norway, there have been earthquakes of relatively large magnitudes (Lurøy earthquake of magnitude 5.8 in 1819, earthquake in Oslo region of magnitude 5.4 in 1904). One of the main concerns is that the recurrence interval for these earthquakes is unknown, due to limited observational period of earthquake records. Extending observational periods and studying reactivation potential of seismogenic faults is therefore the main objective of the following thesis. In total 56 significant faults (in total 184 segments) were identified and studied in six different zones in Norway and the adjacent offshore areas. A dedicated set of criteria are developed and adopted in assessing the reactivation potential of these faults and segments. Reactivation potential of 20 faults (including their segments) were found “possible”, in which only two were assigned “probable”. Among those faults, where reactivation potential was found “possible”, only two faults were found to have a seismogenic potential assessed as “probable”. These are the Øygarden Fault Complex along the coast of Western Norway and the Stuoragurra Fault in Finnmark. Results will be submitted to the European Database for Seismogenic Faults (EDSF). Master's Thesis in Earth Science GEOV399 MAMN-GEOV